Gamifying Language Learning: Improving Primary Students’ Vocabulary Acquisition Using Wordwall - Oktarini, Ni Made Mita; Mahardika, I Gusti Ngurah Agung Wijaya; Oktarina, Putu Santi (New Language Dimensions, 2025)
Vocabulary mastery is a fundamental component of English language proficiency and an essential foundation for young learners. However, in Indonesian EYL classrooms, vocabulary instruction often remains teacher-centered and monotonous, leading to limited engagement and low achievement. This study investigated how Wordwall, a gamified digital platform, could be integrated within a Classroom Action Research (CAR) design to support vocabulary learning. Conducted with 22 fifth-grade students in a primary school, the research followed two CAR cycles, each consisting of planning, action, observation, and reflection. Data were collected through vocabulary tests, classroom observations, and interviews. The findings indicated a steady improvement across cycles. The class mean score increased from 52.72 in the pre-cycle to 71.13 in Cycle I and reached 82.5 in Cycle II. By the end of Cycle II, all students met the Minimum Mastery Criteria (KKM), compared to only six students at baseline. Qualitative observations revealed that while initial use of Wordwall generated interest, uneven participation and low confidence persisted. Adjustments in Cycle II—particularly the incorporation of repetition and structured pair discussions—helped address these issues, resulting in more balanced participation and greater learner confidence. The study concludes that Wordwall can support vocabulary mastery when combined with pedagogical strategies such as recycling input and collaborative learning. These results provide practical guidance for EYL teachers in Indonesia, highlighting how gamified tools can be effectively adapted to classroom realities through iterative, reflective practice.